Framework Perubahan Organisasi yang Adaptif terhadap Dinamika Pasar yang Tidak Menentu karena Perang Dagang - Jopinus Saragih; Adrian K Tarigan; Oktora Jubileus Sinambela (Jurnal Industri Kreatif dan Inovatif, 2025)
This study aims to develop and test an adaptive organizational change framework in response to unstable market dynamics caused by trade wars. Since 2018, escalating global trade conflicts have created a volatile, uncertain, complex, and ambiguous (VUCA) business environment through tariff fluctuations, export–import restrictions, regulatory uncertainty, and disruptions to global supply chains. These effects significantly influence organizational performance, particularly in countries highly dependent on international trade such as Indonesia. The research employs a mixed-methods design with a sequential exploratory approach: qualitative data to construct the framework and quantitative data to validate it. The findings indicate that the impact of the trade war positively affects the need for adaptive organizational change. In addition, environmental scanning capability, organizational structural flexibility, and an adaptive organizational culture enhance adaptation capability and change implementation success. Strategic agility is also found to positively affect organizational performance in a VUCA environment, while the proposed Adaptive Organizational Change Framework (AOCF) effectively improves organizational resilience. The framework implementation further mediates the relationship between environmental pressures and organizational performance. The study produces an AOCF consisting of six main components: Environmental Intelligence System, Adaptive Strategy Formulation, Agile Organizational Structure, Dynamic Resource Management, Change-Ready Culture, and Continuous Learning Mechanism. These components can serve as diagnostic tools and practical guidance for organizations to implement adaptive change.